Accelerated fermentation of chorizo de bilbao by backslopping method - Bolisay, Yolanda B.
This study was conducted in order to accelarate the fermentation process of chorizo de Bilbao by the backsloping method. The study involved the preparation of a controlled chorizo de Bilbao mix using starter organisms, Lactobacillus casei and Saccharomyces cerevisias. Chorizo mixes were backsloped with different level of previously fermented chorizo mix: 100, 200, and 300 grams per kilogram meat. The course of fermentation was followed by the amount of lactic acid produced using pH and % titratable acidity determinations. The experiment have established that the use of Lactobacillus casei at 2.36 x 10^6 cells per gram meat level plus some Saccharomyces crevisiae does not significantly affect the rate of fermentation process. However, backslopping at 200 and 300 gms level accelerate the fermentation process in terms of acid production by 2 days.